Pola Krisis Pada Teks Anekdot Karya Siswa Kelas X SMA PGII 1 Bandung Sebagai Dampak Dari Pembelajaran Menggunakan Model Problem Based Learning - Via, Via Oktarini; Panca Pertiwi Hidayati; Aries Setia Nugraha (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Two causes of difficulties in writing anecdotal texts for students are that they often have difficulty writing innuendo terms that contain humor for the story to be created. Another factor is that educators do not use innovative and creative learning models, and learners do not have enough practice or practice during learning. The purpose of this study is to determine the ability of learners in writing anecdote text, especially determining the structure of anecdote text, namely crisis, by using problem-based learning model as an alternative. The author makes the results of this study after conducting research on students of class X MIPA 6 at SMA PGII 1 Bandung as an experimental class and a control class. The results showed that students in the control class did not have the ability to write a crisis on an anecdote text. This is due to the incompatibility with the characteristics of the crisis of anecdote text, which is satire or criticism on real figures or events that contain humor, silliness, and cuteness that tickle readers. Compared to students in the experimental class who used the problem-based learning model, the results showed that students in the experimental class were able to write a crisis in the anecdote text created because it was in accordance with the characteristics of the crisis, namely satire or criticism of real characters or events that contain humor, silliness, and cuteness that tickle the reader.